Pengaruh Ukuran Perusahaan, Profitabilitas, Kebijakan Deviden, Dan Keputusan Investasi Terhadap Nilai Perusahaan (Studi Penggunaan Indeks LQ-45 Periode 2010 -2014) - Wahyudi, Henri Dwi; Chuzaimah, Chuzaimah; Sugiarti, Dani (Benefit: Jurnal Manajemen dan Bisnis, 2016)
A company aimed and tried to maximize shareholder prosperity. Shareholder prosperity was reflected by company value. This study aimed to review the effect of firm size, Dividend Payout Ratio, Return on Equity, and Price Earning Ratio on firm value among ILQ45 companies registered in The Indonesia Stock Exchange. Populations of this study were firms registered in The Indonesia Stock Exchange of the year 2010 â 2014. The research used purposive sampling method based on determined criteria. There were 22 firms with totally 110 data. After the outliers process, there were 18 with totally 90 data samples. Based on these data, this study carried a classic assumption analysis using multiple regression data with SPSS16. The regression test resulted: (1) Firm size positively influenced and not significant to firm value; (2) Dividend Payout Ratio positively influenced and not significant to firm value; (3) Return on Equity positively influenced and not significant to firm value; (4) Price Earning Ratio positively influenced and not significant to corporate value.